Le passage de l'oral a l'écrit dans Récits des hommes libres, Hamadi - Tomšič, Maja (Acta neophilologica, 2018)
The article presents the process of writing and the historical significance of Récits des hommes libres by Hamadi, a collection of Berber traditional tales. Before addressing the characteristics of this collection, we'll explain a close connection between the Berber liter-ature and its cultural question. The modern Berber literature struggles to preserve its cul-tural heritage. Furthermore, the Berber tales, as part of a long oral tradition, depend above all on the memory of local storytellers and their audience. When writing down Berber tales, that Hamadi had collected in northern Morocco, he translated them from a Berber language to French. Récits des hommes libres reflect a certain orality, characteristics of the Berber storytelling tradition and Hamadi's creativity. Thanks to a rich poetic expression, these tales, adapted to our modern times, transmit the emotion probably evoked by the original storytelling in Berber language.
Keywords: Berber oral tradition; Berberi; Berbers; berbersko ljudsko izročilo; Hamadi; Hamadi; Récits des hommes libree; Récits des hommes libres; tales; the writing of Berber tales; zapis berberskih pripovedi